Soft Skills Required of Business Education Graduates: Perception of Students and Lecturers of Colleges of Education in Oyo State - Oluwalola, K. , Felicia (Kashere Journal of Education, 2021)
The study was conducted to assess the level of students’ and lecturers’ perception to soft skills, identify the difference in the perception of students and lecturers in soft skills and as well identify the difference in the perception of respondents in various colleges of education on the soft skills required of Business Education graduates in Oyo state. Descriptive design of survey type was adopted. The target population for the study were the students and lecturers of Business Education department and two federal and state owned colleges of education in Oyo town were purposively sampled. Forty students in the department of Business Education were randomly selected from each of the three levels in the institutions and ten lecturers were equally selected from each school making a total of 240 students and 20 lecturers. Out of the 240 questionnaires administered, 237 were duly returned. Three research questions were answered and tested at 0.05 level of significance. A questionnaire measuring the perception of students and lecturers was used to gather data from the respondents. Methods of data analysis that were used included frequencies, percentages mean and independent sample t-test. Findings indicate that majority of the students and lecturers are highly perceived on the required soft skills for graduates of Business Education. However, the lecturers had more perception than the students probably due to their level of experience. It was recommended that self-development should be encouraged by the students, schools should introduce acquisition of skills to their curriculum and lecturers should also involve their students in solving uphill tasks in a bid to enhance their practical ability.